MUSALI - A DIVINE HERB WITH ITS MEDICINAL USES (International Journal of Ayurveda and Pharma Research, 2017)
Musali is one of the reputed drug mentioned in the ancient books of Ayurveda and Siddha. It is good for all round development of health Musali is called as Divine Medicine for its medicinal qualities. Musali is also called Talamuli, Suvaha, Talamulika, Deerghakandika, Talapatri in Ayurveda. Acharya Charaka describe Musali in the treatment of respiratory disorders. Sushruta mentioned it in the treatment of Urolithiasis and in the treatment of Chronic obstructive pulmonary disease. In Rajnighantu it has been described as sweet, cooling, mucilaginous, increase Kapha and reduces Pitta daha (burning sensation), act as stimulant, gives strength. It is one of the important Rasayana drugs of Ayurvedic Materia Medica for vigour and vitality. It is an important ingredient of many Ayurvedic preparation and is considered to have aphrodisiac, immunostimulant, hepatoprotective, antioxidant, anticancer and antidiabetic activities. Hence the present study include its general introduction its type, Ayuredic literature, pharmacological activities and variable uses of Musali in several disease.